Synthesis and Preliminary Antibacterial Screening of Hydrazone Derived from Isonicotinic Acid Hydrazide and Its Cu(II), Co(II) and Ni(II) Complexes - Ama, S. O.; Aasegh, T. J.; Ugye, T. J.; Targema, R. D.; Atagher, J. A. (Darul Yasin Al Sys, 2024)
Complexes of Cu(II), Co(II) and Ni(II) derived from the ligand Acetone isonicotinic acid hydrazone (AINH) have been synthesized and characterized on the basis of electronic and physico-chemical methods. The results indicate that all complexes exhibited coordination number of 6 and the ligand coordinated to metal via N and O donor. Analytical data reveal that all the complexes possess 1:2 metal–ligand ratios. Molar conductivity measurements showed non-electrolytic nature of the complexes while the solubility test on the ligand and its metal(II) complexes showed they are soluble in dimethylsulphoxide (DMSO). The complexes were eval_uated for their antibacterial activity against human pathogens like gram positive Staphylococcus aureus (S. aureus), Streptococcus pyogenes (S. pyogenes) and gram negative Escherichia coli (E. coli), Salmonella typhi (S. typhi) strains. The result of microbial screening showed that the complexes have moderate antimicrobial activity.